(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
India embarked on a strategy of economic reforms in the wake of a serious balance of payment crisis in 1991(Mohan, Rakesh 2005). In Indian banking sector, the policy makers adopted a cautious approach for introducing reform measures on the recommendation of Narishmam Committee I (1991), Narishmam Committee II (1997) and Verma Committee (1999). The main objective of the banking sector reforms was to improve the efficiency of banks and to promote a diversified and competitive financial system. One of the outcomes of such reforms was the consolidation of the banking industry through mergers and acquisitions.